Research of Types of Learned Helplessness of Future Specialists in Foreign Philology - Bokhonkova , Yuliia; Tsymbal , Svitlana; Yaremenko , Nataliia; Buhaiova , Nataliia (Insight: the psychological dimensions of society, 2023)
The purpose is to conduct empirical research and theoretically substantiate the types of learned helplessness of future specialists in foreign philology in the context of educational and professional training. The respondents of the empirical research are graduates of the final years of study: students of the fourth year – Bachelor’s degree seekers and students of the second year – Master’s degree seekers, the total number of 432 individuals (M=24.23; SD=±3.08; Me=24; Mo=22). The respondents were majoring in a single or double specialty. Methods. Valid and reliable psychodiagnostic tools that have been adapted and tested were used: “Attributional Style Questionnaire” (ASQ) (Peterson et al., 1982); Ehlers’ questionnaire “Motivation for Achieving Success and Avoiding Failures” (MASAF) (Elers, 2002); the questionnaire “Level of subjective control” (LSC) (Bazhin et al., 1984); Zung Self-Rating Depression Scale (SDS) (Zung, 1965). Results. The provided descriptive statistics confirms that there are no statistically significant differences between the obtained empirical data and the results of similar measurements. Eighteen statistically significant correlations (р
Keywords: students, university, educational space, self-actualization, depression, optimism, pessimism